High Capacity HEVC Video Hiding Algorithm Based on EMD Coded PU Partition Modes - Li, Zhonghao; Meng, Laijin; Jiang, Xinghao; Li, Zhaohong (Symmetry (Basel), 2019)
Data hiding in videos has been a big concern as their rich redundancy can be used for embedding a lot of secret information. Further, as high efficiency video coding (HEVC) introduces many innovative technologies compared with the previous standard, H.264, it has gradually become the mainstream. Therefore, it is valuable to develop new information hiding algorithms by using novel features of HEVC. A HEVC video data hiding algorithm based on prediction unit (PU) partition modes from inter prediction process is proposed in this paper. Firstly, code units (CUs) in two sizes of 8 × 8 and 16 × 16 are selected for embedding, then the PU partition modes in these CUs are coded by a spatial coding method. After that, two specific hiding algorithms by modifying coded PU partition modes in CUs of 8 × 8 and 16 × 16 are proposed, respectively. Experimental results show that the proposed algorithm has achieved excellent performance with high visual quality, and high embedding capacity and low bitrate increase in both high- and low-resolution videos compressed with different quantization parameters (QPs). Compared with the state-of-the-art work, the proposed algorithm achieves a much higher capacity while keeping quite high visual quality with little increase of bitrate.